2012
DOI: 10.1007/s11845-012-0820-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased mean platelet volume in cervicocephalic artery dissections

Abstract: MPV is a marker of platelet function and activation. Increased MPV may be a result of dissection. In addition, it may be a risk factor for dissection-related stroke. Our study supports the notion that platelet reactivity is important in the pathogenesis of the cervicocephalic artery dissections, especially in vertebral artery dissections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…Signs of PLT consumption (low PLT count and/or increased MPV) have been described in uncomplicated abdominal aortic aneurysms [4,5], possibly due to PLT activation within the aneurysmal sac; we documented low PLT count only in AAD. One study showed elevated MPV values in patients with vertebral artery dissection [7]. We noticed only a trend towards lower MPV concentrations but a significant higher ratio of MPV/ PLT in dissection; the latter being more pronounced in type A dissection compared to type B.…”
contrasting
confidence: 62%
“…Signs of PLT consumption (low PLT count and/or increased MPV) have been described in uncomplicated abdominal aortic aneurysms [4,5], possibly due to PLT activation within the aneurysmal sac; we documented low PLT count only in AAD. One study showed elevated MPV values in patients with vertebral artery dissection [7]. We noticed only a trend towards lower MPV concentrations but a significant higher ratio of MPV/ PLT in dissection; the latter being more pronounced in type A dissection compared to type B.…”
contrasting
confidence: 62%
“…Previous studies (11) have shown that patients with acute aortic dissection and aortic aneurysm have lower platelet counts and a higher platelet average volume/platelet count ratio. The related research on the death of dissection shows that the preoperative platelet count is lower and the ratio of platelet average volume to platelet count is higher, which in turn increases the incidence of postoperative complications, increases the postoperative mortality and affects the prognosis (12)(13)(14). The results of this study show that there is a significant difference between the preoperative platelet volume in the postoperative death group and the survival group of patients with dissection, the former is higher than the latter, and the preoperative platelet volume is an independent risk factor for postoperative death, which is predictive for postoperative death risk.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response caused by thrombus formation in the false lumen of aortic dissection can promote platelet activation, further accelerate the consumption of platelets, and ultimately affect the prognosis of patients [ 18 ]. Research has also suggested that platelet function and activity were closely related to cervicocephalic artery dissections [ 19 ]. These conclusions are consistent with our findings that low preoperative platelet count is an independent risk factor for in-hospital mortality in patients with acute type A aortic dissection after surgery.…”
Section: Discussionmentioning
confidence: 99%